Influence of inflammatory bowel disease on intestinal microflora. Issue 12 (December 1978) - Keighley, M R; Arabi, Y; Dimock, F; Burdon, D W; Allan, R N; Alexander-Williams, J
Abstract : The microflora of the jejunum, ileum, and colon has been studied from operative samples in Crohn's disease (n = 30), ulcerative colitis (n = 15), and controls (n = 40). There was no significant difference in the flora of patients with ulcerative colitis compared with controls. In Crohn's disease there was a significant increase in E. coli (P less than 0.001) and B. fragilis (P less than 0.001) in the ileum and of E. coli (P less than 0.001) and lactobacilli (P less than 0.01) in the colon. The abnormal ileal flora in Crohn's disease was unrelated to serological evidence of disease activity (indices: ESR, serum albumin, serum seromucoids), diameter of the ileum, or excision of the ileocaecal valve. The abnormal colonic flora in Crohn's disease was not related to presence of macroscopic colitis.